2010
DOI: 10.1152/ajpheart.00555.2010
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular transsulfuration generates hydrogen sulfide from homocysteine and protects endothelium from redox stress

Abstract: Bearden SE, Beard RS Jr, Pfau JC. Extracellular transsulfuration generates hydrogen sulfide from homocysteine and protects endothelium from redox stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 45 publications
2
53
0
1
Order By: Relevance
“…Consistent with the reduced H 2 S levels, homocysteine levels were lower in MsrA -/ -than in MsrA + / + mice. Recently, Bearden et al reported that extracellular trans-sulfuration from homocysteine to H 2 S protects the endothelium against redox stress (2). Our data suggest that MsrA deficiency alters methionine metabolism and results in reduced homocysteine levels, leading to a sequential reduction in H 2 S production.…”
Section: Fig 5 Levels Of H 2 S In Plasma (A) and Kidneys (B)supporting
confidence: 50%
“…Consistent with the reduced H 2 S levels, homocysteine levels were lower in MsrA -/ -than in MsrA + / + mice. Recently, Bearden et al reported that extracellular trans-sulfuration from homocysteine to H 2 S protects the endothelium against redox stress (2). Our data suggest that MsrA deficiency alters methionine metabolism and results in reduced homocysteine levels, leading to a sequential reduction in H 2 S production.…”
Section: Fig 5 Levels Of H 2 S In Plasma (A) and Kidneys (B)supporting
confidence: 50%
“…This was perhaps one of the mechanisms underlying the H 2 S inhibition of pulmonary arterial remodeling in vivo. As previously demonstrated, H 2 S can also inhibit arterial remodeling by endothelial protection (37) and the induction of the apoptosis of smooth muscle cells (38). In the current study, we mainly investigated the effects of H 2 S on cell proliferation and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 88%
“…Hypoxia appears to increase CBS in the mitochondria (164) and stress-related stimuli can translocate CSE to the mitochondria, although this may take hours (42); additional details are provided in sections ''CBS Translocation to Mitochondria'' and ''CSE Translocation to Mitochondria.'' Initially, it was believed that CBS was predominantly found in the brain and CSE was found in the cardiovascular system [reviewed in Kimura (73)], although a broader distribution is now becoming apparent (6,73,129). H 2 S can also be derived from d-cysteine; however, this appears limited to the brain and kidney, where it protects the former from oxidative stress and the latter from re-perfusion injury (147).…”
Section: Metabolic Relationships Between H 2 S and Omentioning
confidence: 99%